(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Crime against women is becoming an endemic part of our society, and is getting dangerously institutionalized. They are increasingly unsafe, whether within or outside their homes. The waves of shocking atrocities on women that have hit the headlines in recent years indicate only the tip of the iceberg. The scale of violent crimes against women, the frightening regularity with which they occur, the huge increase in sexual crimes being reported from every corner of the nation are pointers to an alarming trend. Crimes against women in Manipur are also showing a significant increase in almost all categories. Under the IPC, which includes violent crimes like rape, molestation, kidnapping and abduction, there has been a steady increase every year. These are the registered cases many cases do not get reported at all. The overall incidence of crimes against children also went up. The disturbing regularity with which women and young girls in Manipur society are subjected to violence and abuse is alarming. Gang-rape, abduction, physical and mental abuse, torture of various kinds, threats of killing and contributed to the growing number of rape are not isolated incidents. Instead, they are a part of the larger systemic problem. The blind consumerist cultures produced by globalization has also reliably sexual attacks on women, child sexual abuse, sex rackets, incidents of sexual blackmailing and so on. With all pervading consumer values promoted through globalization policies there is an increasing trend in the media of commodification of women and there is a spread of serials and films etc. that portray women in a demeaning and degrading way. Domestic violence, including wife beating, murder, mental and physical torture is also growing enormously in recent years. An and domestic violence in particular with a special reference to Manipur Society.